Crosslinkable rubber composition and rubber cushioning material

A crosslinkable rubber composition with acrylonitrile butadiene rubber, inorganic compounds, and tackifier resin addresses durability issues in low-temperature environments, ensuring effective cushioning for nail guns and other devices without size or weight increases.

JP7603104B2Active Publication Date: 2024-12-19DENKA CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023090921
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-06-01
Publication Date
2024-12-19
Estimated Expiration
2043-06-01

AI Technical Summary

Technical Problem

Rubber cushioning materials used in devices like nail guns become hard and lose durability in low-temperature environments, leading to potential air leakage and damage, and enlarging the material to improve impact resistance increases equipment size and weight.

Method used

A crosslinkable rubber composition comprising 100 parts by mass of acrylonitrile butadiene rubber, 50 to 300 parts by mass of a particulate inorganic compound, 1 to 50 parts by mass of a tackifier resin, and 0.1 to 10 parts by mass of a crosslinking agent, optimized for low-temperature durability.

Benefits of technology

The composition provides a rubber cushioning material with excellent durability in low-temperature environments, suitable for nail guns and other devices with repeated impacts, without increasing size or weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603104000007
    Figure 0007603104000007
  • Figure 0007603104000008
    Figure 0007603104000008
  • Figure 0007603104000001
    Figure 0007603104000001
Patent Text Reader

Abstract

To provide a crosslinkable rubber composition from which a rubber cushioning material excellent in durability even under low temperature environment can be obtained, and a rubber cushioning material obtained by crosslinking the same.SOLUTION: A crosslinkable rubber composition contains 100 pts.mass of a rubber component containing acrylonitrile-butadiene-based rubber, 50 to 300 pts.mass of a particulate inorganic compound, 1 to 50 pts.mass of a tackifier resin, and 0.1 to 10 pts.mass of a crosslinking agent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a crosslinkable rubber composition, more particularly to a composition containing an acrylonitrile butadiene rubber having excellent durability (impact resistance) against repeated impacts in a low-temperature environment. The present invention also relates to a rubber cushioning material using the crosslinkable rubber composition. [Background technology]

[0002] A rubber shock absorber (hereinafter referred to as a "rubber shock absorber") is a component that is incorporated into devices or tools to absorb shocks caused by other moving components. An example of such a device or tool is a nail gun that uses air pressure to drive a piston inside a cylinder to drive nails, needles, screws, etc. A nail gun is equipped with a cylindrical rubber shock absorber called a bumper to absorb shocks caused by repeated piston movements.

[0003] The rubber cushioning is also a packing component that prevents air from leaking out of the piston, and if the rubber cushioning is damaged, air will leak out, preventing the piston from returning or damaging the nail gun itself. To prevent such air leaks and damage, the rubber cushioning needs to be replaced as needed, but to reduce the effort and cost of replacement, it needs to have excellent durability (impact resistance) against repeated impacts.

[0004] One possible way to improve the impact resistance of rubber cushioning materials is to increase the size of the materials, but this would result in the devices and tools used to make them larger and heavier. From the perspective of reducing the size of nail guns, increasing the size of rubber cushioning materials is not desirable.

[0005] In Patent Documents 1 and 2, attempts are made to improve impact resistance by changing the shape of the rubber cushioning material.

[0006] Moreover, Patent Document 3 proposes a crosslinkable rubber composition for a buffer material, which contains a rubber component including an acrylonitrile butadiene rubber, and a specific crosslinking accelerator and crosslinking retarder. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-049441 A [Patent Document 2] JP 2002-103246 A [Patent Document 3] JP 2014-159506 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, when working in low temperature environments (for example, below 5°C), the rubber cushioning material itself can become hard, posing durability issues.

[0009] An object of the present invention is to provide a crosslinkable rubber composition which can give a rubber cushioning material having excellent durability even in a low-temperature environment, and a rubber cushioning material obtained by crosslinking the same. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a composition with a specific blend ratio, which has led to the completion of the present invention.

[0011] That is, according to the present invention, the following inventions are provided. [1] A cross-linkable rubber composition comprising 100 parts by mass of a rubber component containing an acrylonitrile butadiene rubber, 50 to 300 parts by mass of a particulate inorganic compound, 1 to 50 parts by mass of a tackifier resin, and 0.1 to 10 parts by mass of a cross-linking agent. [2] The cross-linkable rubber composition according to [1], wherein the acrylonitrile butadiene rubber has an acrylonitrile content of 16 to 30 mass %. [3] The crosslinkable rubber composition according to [1] or [2], wherein the acrylonitrile butadiene rubber comprises an acrylonitrile butadiene rubber and / or a hydrogenated acrylonitrile butadiene rubber. [4] The crosslinkable rubber composition according to any one of [1] to [3], wherein the particulate inorganic compound contains carbon black and / or silica. [5] The crosslinkable rubber composition according to any one of [1] to [4], wherein the tackifier resin contains a resin having an aromatic skeleton. [6] The crosslinkable rubber composition according to any one of [1] to [5], which is used for a rubber cushioning material for absorbing impact. [7] The crosslinkable rubber composition according to any one of [1] to [6], which is used as a rubber cushioning material for absorbing impact caused by a piston of a nail gun. [8] A rubber cushioning material which is a crosslinked product of the crosslinkable rubber composition according to any one of [1] to [7]. Effect of the Invention

[0012] According to the crosslinkable rubber composition of the present invention, it is possible to provide a crosslinkable rubber composition which can give a rubber cushioning material having excellent durability even in a low-temperature environment, and a rubber cushioning material obtained by crosslinking the crosslinkable rubber composition.

[0013] The crosslinked product obtained by crosslinking the crosslinkable rubber composition according to the present invention can be used for various purposes as a rubber cushioning material, and is particularly suitable for use as a cushioning material for nail guns. The rubber cushioning material can also be used as a cushioning material to be installed in other devices or tools at locations where repeated impacts occur. The rubber cushioning material is also effective as a cushioning material for devices or tools using hydraulic cylinders, since the acrylonitrile butadiene rubber has excellent oil resistance. [Brief description of the drawings]

[0014] [Figure 1] FIG. 13 is a diagram illustrating a method for producing a joint for a flexibility test. [Diagram 2]FIG. 13 is a diagram illustrating the bending direction and angle θ of the joint for flexibility test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Crosslinkable Rubber Composition> The crosslinkable rubber composition of the present invention is a crosslinkable rubber composition for a buffer material, which contains acrylonitrile butadiene rubber, a particulate inorganic compound, a tackifier resin, and a crosslinking agent. Each component contained in the crosslinkable rubber composition of the present invention and optional components will be described in detail below.

[0016] <Rubber component> The rubber component includes an acrylonitrile butadiene rubber. The acrylonitrile butadiene rubber includes an acrylonitrile butadiene rubber (hereinafter also referred to as "NRB") and / or a hydrogenated acrylonitrile butadiene rubber (hereinafter also referred to as "hydrogenated NBR"). By using the acrylonitrile butadiene rubber or the hydrogenated acrylonitrile butadiene rubber, a crosslinkable rubber composition can be produced at a lower cost than when urethane is used.

[0017] The content of the acrylonitrile-derived structural unit in the acrylonitrile-butadiene rubber is preferably 16 to 34% by mass, more preferably 17 to 24% by mass. The content of the acrylonitrile-derived structural unit is specifically, for example, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34% by mass, and may be within any two of the numerical values ​​exemplified here. When the content of the acrylonitrile-derived structural unit is within this range, it is possible to obtain a crosslinkable rubber composition having good flexibility at low temperatures and excellent durability in a low-temperature environment. In addition, when the acrylonitrile-butadiene rubber contains a plurality of acrylonitrile-butadiene rubbers (for example, two types of NBR, or both NRB and hydrogenated NBR), the content is the total content of the acrylonitrile-derived structural unit contained therein.

[0018] NBR is a polymer obtained by copolymerizing monomer raw materials containing acrylonitrile and butadiene, and has a structural unit derived from acrylonitrile and a structural unit derived from butadiene. NBR may have only a structural unit derived from acrylonitrile and a structural unit derived from butadiene as a structural unit derived from a monomer, but may also contain a structural unit derived from other monomers other than these. Specific examples of other monomers include, for example, ethylenically unsaturated carboxylic acids such as (meth)acrylic acid; esters of ethylenically unsaturated carboxylic acids (e.g., alkyl esters); and isoprene. By copolymerizing other monomers, it may be possible to further improve the crosslinking characteristics of the rubber composition and the impact resistance, tensile strength, hardness, etc. of the obtained buffer material. Only one type of other monomer may be used, or two or more types may be used in combination.

[0019] The content of the structural units derived from the other monomers in NBR is, for example, 20% by mass or less, preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less. The content of the structural units derived from the other monomers in NBR is, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20% by mass, and may be within a range between any two of the numerical values ​​exemplified here. Hydrogenated NBR is a rubber in which a part of the structural units derived from butadiene in the above-mentioned NBR is hydrogenated. The amount of hydrogenation is expressed as an iodine value, and preferably the iodine value is in the range of 8 to 57 mg / 100 mg. In addition, when the acrylonitrile-butadiene rubber contains a plurality of acrylonitrile-butadiene rubbers (for example, two types of NBR, or both NBR and hydrogenated NBR), the content of the structural unit derived from the other monomer is the total content of the structural units derived from the other monomer contained therein.

[0020] The rubber component may contain other rubber components other than acrylonitrile butadiene rubber. Specific examples of other rubber components include, for example, ethylene-propylene-diene rubber (EPDM), ethylene-propylene rubber (EPM), urethane rubber, butyl rubber (IIR), fluororubber (FKM), and silicone rubber (Q). Only one type of other rubber component may be used, or two or more types may be used in combination.

[0021] The rubber component contains acrylonitrile butadiene rubber in an amount of preferably 70 to 100% by mass, more preferably 85 to 100% by mass, and even more preferably 95 to 100% by mass. The content of the acrylonitrile butadiene rubber in the rubber component is specifically, for example, 70, 75, 80, 85, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, or 100% by mass, and may be within a range between any two of the numerical values ​​exemplified here. In addition, the content of other rubber components is preferably within a range that does not impair the purpose or effects of the present invention. Specifically, the content of other rubber components in the rubber component is preferably 30% by mass or less, more preferably 15% by mass or less, even more preferably 5% by mass or less, and particularly preferably 0% by mass.

[0022] <Particulate inorganic compounds> The shape of the particulate inorganic compound may be, for example, a sphere, an elliptical sphere, a cube, a rectangular parallelepiped, or a random shape, and may be hollow or solid. The average particle size of the particulate inorganic compound is, for example, 10 nm to 1000 μm, preferably 30 nm to 500 μm, more preferably 40 nm to 300 μm, and even more preferably 50 nm to 100 μm. The "average particle size" refers to the particle size at an integrated value of 50% in the particle size distribution determined by a laser diffraction / scattering method. These may be used alone or in combination of two or more.

[0023] Examples of particulate inorganic compounds include metal oxides such as alumina, silica, aluminosilicate, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, and ferrites; hydrated inorganic substances such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and hydrotalcite; metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate; calcium salts such as calcium sulfate and calcium silicate; glass beads, silica-based balloons, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon balloons, charcoal powder, and various metals. Examples of the clay minerals include powder, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, zinc borate, various magnetic powders, fly ash, inorganic hollow fillers, pearlite, obsidian, pearlite, rosin, diatomaceous earth, dewatered sludge, boron, sodium tetraborate hydrate (borax), phosphoric acid compounds, smectite, bentonite, montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, hectorite, stevensite, and other smectite clay minerals; sericite, illite, glauconite, chlorite, talc, powdered glass, and the like. These may be used alone or in combination of two or more.

[0024] In particular, the crosslinkable rubber composition of the present invention preferably contains carbon black and / or silica.

[0025] The content of the particulate inorganic compound is 50 to 300 parts by mass, preferably 60 to 260 parts by mass, and more preferably 70 to 210 parts by mass, relative to 100 parts by weight of the rubber component. If the content of the particulate inorganic compound is less than 50 parts by mass, the hardness may be low, and if the content of the particulate inorganic compound is more than 250 parts by mass, the hardness may be too high and the flexibility may be poor. The content of the particulate inorganic compound is, for example, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, or 300 parts by mass relative to 100 parts by weight of the rubber component, and may be within the range between any two of the numerical values ​​exemplified here.

[0026] <Tackifier resin> Examples of tackifier resins include rosin resins, hydrogenated rosin resins, terpene resins, hydrogenated terpene resins, aromatic modified terpene resins, terpene phenol resins, phenol resins, styrene resins, coumarone resins, phenol formaldehyde resins, asphalt, C5 petroleum resins (aliphatic carbonized resins) obtained by copolymerizing C5 fractions such as pentene, isoprene, piperine, and 1,3-pentadiene produced by thermal decomposition of petroleum naphtha, C9 petroleum resins (aromatic hydrocarbon resins) obtained by copolymerizing C9 fractions such as indene and vinyltoluene produced by thermal decomposition of petroleum naphtha, C5 / C9 petroleum resins (alicyclic hydrocarbon resins), and hydrogenated petroleum resins and alicyclic saturated hydrocarbon resins obtained by hydrogenating these petroleum resins. These may be used alone or in combination of two or more.

[0027] In particular, the crosslinkable rubber composition of the present invention preferably contains a resin having an aromatic skeleton, such as a coumarone resin, a phenol resin, a terpene phenol resin, a phenol formaldehyde resin, a C9 petroleum resin (aromatic resin), or a C5 / C9 petroleum resin (alicyclic hydrocarbon resin).

[0028] The content of the tackifier resin is 1 to 50 parts by mass, preferably 3 to 40 parts by mass, and more preferably 6 to 25 parts by mass, based on 100 parts by weight of the rubber component. If the content of the tackifier resin is less than 1 part by mass, the flexibility at low temperatures may be poor, and if the content of the tackifier resin is more than 50 parts by mass, the hardness and deformation resistance may be reduced, and stickiness may occur, resulting in poor durability at room temperature. The content of the tackifier resin is, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, or 50 parts by weight based on 100 parts by weight of the rubber component, and may be within a range between any two of the numerical values ​​exemplified here.

[0029] <Crosslinking agent> The crosslinkable rubber composition of the present invention contains a crosslinking agent. As the crosslinking agent, a sulfur-based crosslinking agent, an organic peroxide crosslinking agent, etc. can be used. Only one type of crosslinking agent may be used, or two or more types may be used in combination.

[0030] Examples of the sulfur-based crosslinking agent include sulfur such as powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, and insoluble sulfur; and sulfur compounds such as sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, and polymer polysulfide. Only one type of sulfur-based crosslinking agent may be used, or two or more types may be used in combination.

[0031] Examples of organic peroxide crosslinking agents include dicumyl peroxide, t-butyl dicumyl peroxide, 2,4-dichlorobenzoyl peroxide, di-t-butyl peroxide, t-butyl dicumyl peroxide, benzoyl peroxide, acetyl peroxide, isobutyryl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, Examples of the organic peroxide crosslinking agent include α,α'-bis(t-butylperoxyisopropyl)benzene, t-butylperoxyisopropylcarbonate, parachlorobenzoyl peroxide, t-butylperbenzoate, 3,3,5-trimethylhexanone peroxide, n-butyl-4,4-bis(t-butylperoxy)valerate, di-sec-butylperoxydicarbonate, 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-butylperoxy)cyclododecane, etc. Only one organic peroxide crosslinking agent may be used, or two or more organic peroxide crosslinking agents may be used in combination.

[0032] The content of the crosslinking agent is 0.1 to 10 parts by mass, preferably 0.7 to 8 parts by mass, and more preferably 1.3 to 5 parts by mass, relative to 100 parts by weight of the rubber component. If the content of the crosslinking agent is less than 0.1 parts by mass, the hardness and resistance to deformation may be deteriorated, and if the content of the crosslinking agent is more than 10 parts by mass, the rubber may be too hard and have poor flexibility. The content of the crosslinking agent is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 parts by mass relative to 100 parts by weight of the rubber component, and may be within a range between any two of the numerical values ​​exemplified here.

[0033] <Other ingredients> The crosslinkable rubber composition of the present invention may contain other components other than the above-mentioned components as necessary. Examples of the other components include additives such as fibrous compounds, crosslinking accelerators, crosslinking retarders, co-crosslinking agents, antioxidants, antioxidants, processing aids (stearic acid, zinc oxide, etc.), stabilizers, tackifiers, silane coupling agents, plasticizers, flame retardants, release agents, waxes, and lubricants. The additives may be used alone or in combination of two or more.

[0034] The fibrous compound may have any shape as long as it is fibrous, and the cross-sectional shape of the fibrous compound may be, for example, circular, elliptical, or polygonal. The ratio L / D of the length L to the diameter D of the fibrous compound is, for example, more than 10, preferably 50 or more, and more preferably 100 or more. The upper limit of L / D is not particularly specified, but is, for example, 10,000. The diameter D of the fibrous compound is, for example, 1 to 100 μm, preferably 2 to 50 μm, and more preferably 5 to 20 μm. The length L of the fibrous compound is, for example, 0.05 to 10 mm, preferably 0.1 to 8 mm, and more preferably 0.2 to 5 mm. There are two types of fibrous compounds: inorganic fibrous compounds and organic fibrous compounds. Only one type of fibrous compound may be used, or two or more types may be used in combination.

[0035] Examples of inorganic fiber compounds include glass fibers (E glass fibers, C glass fibers, S glass fibers, D glass fibers), rock wool, ceramic fibers (silica alumina fibers, alumina fibers, silica fibers), zirconia fibers, carbon fibers, bulk alkaline earth silicate fibers, gypsum fibers, carbon fibers, metal fibers, slag fibers, and basalt fibers.

[0036] Examples of the organic fiber compound include meta-aramid fiber, para-aramid fiber, amide fiber, pulp fiber, cellulose fiber, polyparaphenylene benzobisoxazole fiber, polyarylate fiber, and the like.

[0037] Specific examples of the crosslinking accelerator include di-2-benzothiazolyl disulfide, N-cyclohexyl-2-benzothiazolyl sulfenamide, and tetraalkylthiuram disulfide. It is possible to add no crosslinking accelerator or only a very small amount (for example, less than 1 part by mass per 100 parts by weight of the rubber component), but in one embodiment, the content of the crosslinking accelerator may be 0.05 to 10 parts by mass, more preferably 0.1 to 8 parts by mass, and even more preferably 0.2 to 5 parts by mass per 100 parts by weight of the rubber component, for the purpose of adjusting the crosslinking rate.

[0038] Specific examples of the crosslinking retarder include thioimide derivatives such as N-(cyclohexylthio)phthalimide, N-(2-ethylhexylthio)phthalimide, N-(cyclohexylthio)maleimide, and N-(4-t-butylphenylthio)succinimide; aromatic monocarboxylic acids such as benzoic acid and salicylic acid; amide derivatives such as N-isopropylthio-N-cyclohexyl-benzothiazyl-2-sulfonamide, N-cyclohexyl-N-trichloromethylthio-benzyl-2-sulfonamide, and N-phenyl-N-trichloromethylthiobenzenesulfonamide; aromatic dicarboxylic acids such as orthophthalic acid, phthalic anhydride, isophthalic acid, and terephthalic acid, or their acid anhydrides. Only one type of crosslinking retarder may be used, or two or more types may be used in combination.

[0039] Specific examples of the co-crosslinking agent include quinone dioxime, ethylene glycol dimethacrylate, divinylbenzene, diallyl phthalate, triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, 1,2-polybutadiene, metal methacrylates, metal acrylates, etc. Only one type of co-crosslinking agent may be used, or two or more types may be used in combination.

[0040] Specific examples of the antiaging agent include phenol derivatives, aromatic amine derivatives, amine-ketone condensates, benzimidazole derivatives, dithiocarbamic acid derivatives, thiourea derivatives, etc. The antiaging agent may be used alone or in combination of two or more kinds.

[0041] The crosslinkable rubber composition of the present invention can be prepared by uniformly kneading the above-mentioned components. As the kneading machine, for example, a conventionally known one such as a mixing roll, a pressure kneader, an internal mixer (Banbury mixer), etc. can be used. In this case, among the various blending components, the components other than the components that contribute to the crosslinking reaction (crosslinking accelerator, crosslinking retarder, crosslinking agent, etc.) may be uniformly kneaded first, and then the components that contribute to the crosslinking reaction may be kneaded.

[0042] <Rubber cushioning material> The rubber cushioning material of the present invention is a molded article made of a crosslinked product of the crosslinkable rubber composition of the present invention. The rubber cushioning material can be produced by crosslinking (vulcanizing) and molding the crosslinkable rubber composition. As a method for crosslinking and molding the rubber cushioning material, a conventionally known method such as injection molding, compression molding, and transfer molding can be used.

[0043] The heating temperature (crosslinking temperature) during molding is, for example, about 100 to 200° C., and the heating time (crosslinking time) is, for example, about 0.5 to 120 minutes.

[0044] The crosslinked product obtained by crosslinking the crosslinkable rubber composition according to the present invention can be used for various purposes as a rubber cushioning material, and is particularly suitable for use as a cushioning material for nail guns. The rubber cushioning material can also be used as a cushioning material to be installed in other devices or tools at locations where repeated impacts occur. The rubber cushioning material is also effective as a cushioning material for devices or tools using hydraulic cylinders, since the acrylonitrile butadiene rubber has excellent oil resistance. EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these.

[0046] <Preparation of crosslinkable rubber composition and production of rubber cushioning material> A crosslinkable rubber composition was prepared, and a rubber cushioning material was produced using the prepared crosslinkable rubber composition. First, according to the compounding compositions shown in Tables 1 to 6 (the unit of compounding amount in the tables is parts by mass), a predetermined amount of rubber component (NBR / hydrogenated NBR), particulate inorganic compound, and tackifier resin were kneaded with a pressure kneader. At this time, the rotation speed of the pressure kneader was 30 rpm, and the kneading time was the time until the maximum temperature of the kneaded material reached 120°C. After cooling, a crosslinking agent was added to the obtained kneaded material, and the kneading was performed with a mixing roll to prepare a crosslinkable rubber composition.

[0047] Next, the obtained crosslinkable rubber composition was molded and crosslinked at a temperature of 160 to 180° C. using a compression (direct pressure) molding machine to obtain a rubber cushioning material (test specimen).

[0048] [Table 1]

[0049] [Table 2]

[0050] [Table 3]

[0051] [Table 4]

[0052] [Table 5]

[0053] [Table 6]

[0054] Details of each component used in the examples and comparative examples are as follows. <Rubber component> NBR15: "N260S" manufactured by JSR Corporation, 15% acrylonitrile by mass NBR16: A mixture of 68 parts by mass of "N260N" and 32 parts by mass of "Nipol DN401": 16% by mass of acrylonitrile NBR17: A mixture of 34 parts by mass of "N260N" and 66 parts by mass of "Nipol DN401": 17% by mass of acrylonitrile NBR18: NBR: "Nipol DN401" manufactured by Zeon Corporation, 18% acrylonitrile by mass NBR19.5: "N250S" manufactured by JSR Corporation, acrylonitrile content 19.5% by mass NBR21: A mixture of 57 parts by mass of "Nipol DN401" and 43 parts by mass of "N240S": 21% by mass of acrylonitrile NBR22: A mixture of 43 parts by mass of "Nipol DN401" and 57 parts by mass of "N240S": 22% by mass of acrylonitrile NBR23: A mixture of 28 parts by mass of "Nipol DN401" and 72 parts by mass of "N240S": 23% by mass of acrylonitrile NBR24: A mixture of 15 parts by mass of "Nipol DN401" and 85 parts by mass of "N240S": 24% by mass of acrylonitrile NBR25: "N240S" manufactured by JSR Corporation, acrylonitrile content 25% by mass NBR26: "N640" manufactured by JSR Corporation, acrylonitrile content 26% by mass NBR28: ​​"Nipol DN2850" manufactured by Zeon Corporation, 28% acrylonitrile by mass NBR29: "N241" manufactured by JSR Corporation, acrylonitrile content 29% by mass NBR33.5: "Nipol 1042" manufactured by Zeon Corporation, 33.5% by mass of acrylonitrile NBR35: "Nipol DN1201" manufactured by Zeon Corporation, 35% acrylonitrile by mass Hydrogenated NBR (HNBR18.6): Zeon Corporation's "Zetpol 4310", acrylonitrile content 18.6% by mass, iodine value 15mg / 100mg Hydrogenated NBR (HNBR23.6): Zeon Corporation's "Zetpol 3310", acrylonitrile content 23.6% by mass, iodine value 15 mg / 100 mg Hydrogenated NBR (HNBR29): A mixture of 41 parts by mass of "Zetpol 4310" and 59 parts by mass of "Zetpol 2030L": 29% by mass of acrylonitrile *Zetpol 2030L contains 36.2% acrylonitrile by mass and has an iodine value of 56.6 mg / 100 mg. <Particulate inorganic compounds> Carbon black: Asahi Carbon #15, manufactured by Asahi Carbon Co., Ltd., average particle size 122 nm Silica: Tosoh Silica Corporation "Nipsil VN3", average particle size 18μm Aluminum hydroxide: "C-301N" manufactured by Sumitomo Chemical Co., Ltd., average particle size 1.5 μm <Tackifier resin> Coumarone resin: "Cumarone G-90" manufactured by Nippon Paint Chemical Co., Ltd., softening point 90℃ Phenolic resin: Showa Denko Materials Co., Ltd. "PR1501", softening point 85~100℃ Terpene phenol resin: "YS Polystar T80" manufactured by Yasuhara Chemical Co., Ltd., softening point 80℃ Aliphatic hydrocarbon resin (C5): Zeon Corporation's Quintone M100, softening point 95°C <Crosslinking agent> Sulfur: manufactured by Hosoi Chemical Industry Co., Ltd.

[0055] <Evaluation of rubber cushioning materials> For the obtained rubber cushioning material (test specimen), the following items were measured and evaluated. The results are shown together in Tables 1 to 6.

[0056] Under the environment of 21°C, three sheet-shaped test specimens with a thickness of 2 mm were stacked, and in accordance with JIS K6253-3, the hardness was measured using a Type A durometer hardness tester. ◎: 75 or more 〇: 70 or more and less than 75 △: 65 or more and less than 70 ×: Less than 65

[0057] <Normal temperature flexibility> As shown in Figure 1, prepare two pieces of SUS plates with a thickness of 1 mm, a width of 25 mm, and a length of 100 mm with double-sided tape attached, and arrange them side by side with a 3-mm interval in the length direction. Then attach a sheet-shaped test specimen with a thickness of 2 mm, a width of 10 mm, and a length of 100 mm. And as shown in Figure 2, the bonded body after bonding was bent at 21°C in the environment in the direction opposite to the surface where the test specimen was attached, and the angle θ at the time when cracks appeared in the test specimen was measured, and the flexibility was judged according to the following criteria. Note that the larger the angle when cracks appear, the better the flexibility. ◎: No cracks even at an angle of 180 degrees (described as ">180" in the row of crack generation angle in the table) ○: Cracks occur at an angle of 160 degrees or more and less than 180 degrees △: Cracks occur at an angle of 140 degrees or more and less than 160 degrees ×: Cracks occur at an angle of less than 140 degrees

[0058] <Low temperature flexibility> As shown in Figure 1, two SUS plates with a thickness of 1 mm, width of 25 mm, and length of 100 mm were prepared with double-sided tape attached, and placed side by side with a 3 mm gap in the length direction. A sheet-shaped test specimen with a thickness of 2 mm, width of 10 mm, and length of 100 mm was attached to the two plates. Then, as shown in Figure 2, the bonded joint was folded in the opposite direction to the side to which the test specimen was attached in an environment of 0°C, and the angle θ at which a crack appeared in the test specimen was measured, and the flexibility was evaluated according to the following criteria. Note that the larger the angle at which the crack appeared, the better the flexibility. ◎: No cracks even at an angle of 180 degrees (the crack angle row in the table reads ">180") ○: Cracks occur at angles between 160 degrees and 180 degrees △: Cracks occur at angles between 140 degrees and 160 degrees ×: Cracks occur at angles less than 140 degrees

[0059] <Deformation resistance> A gauge line with a length between the gauge lines of 50 mm (original gauge line length) was drawn on a sheet-like specimen with a thickness of 2 mm, width of 10 mm, and length of 150 mm. It was clamped between 100 mm chucks and pulled at a speed of 500 mm / min in an environment of 21°C until the gauge line length became 100 mm, and left in that state for 1 minute. The specimen was then removed and left on a flat surface for 10 minutes. The gauge line length (final gauge line length) of the specimen after leaving it was measured, and the deformation resistance was calculated using the following formula. (Final gauge length - original gauge length 50 mm) ÷ (original gauge length 50 mm) x 100 ◎: Less than 20% ※(60-50)÷50×100=20% ○: 20% or more but less than 30% ※(65-50)÷50×100=30% △: 30% or more but less than 40% *(70-50)÷50×100=40% ×: 40% or more

[0060] <Number of times it can be used at room temperature> A cushioning material test piece molded into a specified cylindrical shape was attached to a commercially available nail gun [a general nail gun with a specified supply pressure of 0.3 to 0.8 MPa], and an operation test was performed under conditions of a 21°C environment, a supply air pressure of 0.7 MPa, and a piston speed of approximately 1.2 seconds / cycle, and the number of piston operation cycles until the piston no longer operated normally was measured, and this was taken as the service life at room temperature. Note that stickiness occurred in Comparative Example 4 (※1). ◎: 4 million or more times ○: 3.5 million or more, less than 4 million △: 3 million or more, less than 3.5 million ×: Less than 3 million times

[0061] <Low temperature durability> A cushioning material test specimen molded into a specified cylindrical shape was attached to a commercially available nail gun (a general nail gun with a specified supply pressure of 0.3 to 0.8 MPa) and an operation test was carried out in an environment of 0°C under conditions of a supply air pressure of 0.7 MPa and a piston speed of approximately 1.2 seconds / cycle. The number of piston operation cycles until the piston no longer operated normally was measured and this was regarded as the service life at low temperatures. ◎: 3 million times or more ○: 2.5 million or more, less than 3 million △: 2 million or more, less than 2.5 million ×: Less than 2 million times

[0062] Whether or not the piston had stopped functioning normally was judged based on whether normal operation of the piston had been hindered by a broken piece of rubber cushioning getting caught in the piston seal, a decrease in the lubricating effect of the lubricant due to wear powder of the cushioning, air leakage, etc. The rubber cushioning deteriorates or becomes damaged due to repeated impacts from the piston operation, and when the degree of deterioration exceeds a certain limit, a factor that hinders piston operation occurs.

Claims

1. 100 parts by mass of a rubber component containing an acrylonitrile butadiene rubber; 50 to 300 parts by mass of a particulate inorganic compound; 1 to 50 parts by weight of a tackifier resin; 0.1 to 10 parts by weight of a crosslinking agent; A crosslinkable rubber composition comprising: A crosslinkable rubber composition used in rubber cushioning materials for absorbing shock.

2. 100 parts by mass of a rubber component containing 91 to 100% by mass of an acrylonitrile butadiene rubber; 50 to 300 parts by mass of a particulate inorganic compound; 1 to 50 parts by weight of a tackifier resin; 0.1 to 10 parts by weight of a crosslinking agent; A crosslinkable rubber composition comprising:

3. 100 parts by mass of a rubber component containing 70 to 100% by mass of an acrylonitrile butadiene rubber; 50 to 300 parts by mass of a particulate inorganic compound; 1 to 50 parts by weight of a tackifier resin; 0.1 to 10 parts by weight of a crosslinking agent; A crosslinkable rubber composition comprising:

4. 100 parts by mass of a rubber component containing 70 to 100% by mass of an acrylonitrile butadiene rubber; 50 to 300 parts by mass of a particulate inorganic compound; 1 to 50 parts by weight of a tackifier resin; 0.1 to 10 parts by weight of a crosslinking agent; A crosslinkable rubber composition comprising the above rubber component (excluding those containing 10 to 70 mass % of a styrene-butadiene copolymer).

5. The crosslinkable rubber composition according to any one of claims 1 to 4, wherein the acrylonitrile butadiene rubber has an acrylonitrile content of 16 to 30 mass%.

6. The crosslinkable rubber composition according to any one of claims 1 to 4, wherein the acrylonitrile butadiene rubber comprises an acrylonitrile butadiene rubber and / or a hydrogenated acrylonitrile butadiene rubber.

7. The crosslinkable rubber composition according to any one of claims 1 to 4, wherein the particulate inorganic compound contains carbon black and / or silica.

8. The crosslinkable rubber composition according to any one of claims 1 to 4, wherein the tackifier resin comprises a resin having an aromatic skeleton.

9. The crosslinkable rubber composition according to any one of claims 1 to 4, which is used as a rubber cushioning material for absorbing impact caused by a piston of a nail driver.

10. A rubber cushioning material which is a crosslinked product of the crosslinkable rubber composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Cushioning mechanism in air-operated nailing machine

    JP2002103246A

  • Power tool and shock-absorbing mechanism

    JP2008049441A

  • Damping material

    JP2009197115A

  • High damping composition

    JP2011132481A

  • Crosslinking rubber composition for cushioning material and cushioning material using the same

    JP2014159506A